Beauty Ideology in Latin America - de Casanova, Erynn Masi (2018)
While empirical studies provide details about the local practices and interpretations of beauty, it makes sense to discuss Latin American beauty ideology or ideologies in general because of the shared history of colonialism and the way that beauty images travel easily across national borders in this region today. These images do not dictate, but do inform, the way that women (and men) fashion their bodies in Latin American societies. The purpose of this essay is to develop a theory of Latin American beauty ideologies that is grounded in but moves beyond the empirical research on this topic. Rather than providing an exhaustive typology, I suggest some concepts worth considering, with the aim of stimulating academic debate and discussion. I identify two main aspects of beauty ideology: 1) the embrace of artificiality; and 2) racial mobility.